2018
DOI: 10.1103/physrevx.8.021025
|View full text |Cite
|
Sign up to set email alerts
|

Cell Growth Rate Dictates the Onset of Glass to Fluidlike Transition and Long Time Superdiffusion in an Evolving Cell Colony

Abstract: Collective migration dominates many phenomena, from cell movement in living systems to abiotic selfpropelling particles. Focusing on the early stages of tumor evolution, we enunciate the principles involved in cell dynamics and highlight their implications in understanding similar behavior in seemingly unrelated soft glassy materials and possibly chemokine-induced migration of CD8 þ T cells. We performed simulations of tumor invasion using a minimal three-dimensional model, accounting for cell elasticity and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
159
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(167 citation statements)
references
References 76 publications
1
159
0
Order By: Relevance
“…We have used simulations of a minimal model [23] to analyze the experimental results [15], The sluggish cell dynamics in the core is reminiscent of relaxation in supercooled liquids as they undergo a transition to a glassy state [31]. Using concepts from glass transition theory, we showed that higher order susceptibility for cells near the tumor periphery in experiments, which are fully accounted for in the simulations, shows a peak at t ≈ 5.6…”
Section: Discussionmentioning
confidence: 99%
“…We have used simulations of a minimal model [23] to analyze the experimental results [15], The sluggish cell dynamics in the core is reminiscent of relaxation in supercooled liquids as they undergo a transition to a glassy state [31]. Using concepts from glass transition theory, we showed that higher order susceptibility for cells near the tumor periphery in experiments, which are fully accounted for in the simulations, shows a peak at t ≈ 5.6…”
Section: Discussionmentioning
confidence: 99%
“…Simulations: In order to test the theoretical predictions, we simulated a three dimensional MCS with embedded, mobile TPs. As in our previous studies, [12,14,15], we used an agent-based model to simulate To study the dynamics of TPs, we account for the CC-CC, CC-TP and TP-TP interactions. We model the interactions using two potentials (Gaussian and Hertz scheme) to ensure that the qualitative results are independent of the nature of the potential (See the details in the SI).…”
Section: Pacs Numbersmentioning
confidence: 99%
“…We model the interactions using two potentials (Gaussian and Hertz scheme) to ensure that the qualitative results are independent of the nature of the potential (See the details in the SI). The equation of motion governing the dynamics of TP and CCs is taken to be,˙ r i = Fi γi , where˙ r i is the velocity of i th CC or TP, F i is the force on i th CC/TP, and γ i represents the damping term (for details see reference [12]). The simulations are performed in the over-damped limit (see [12] and the SI for details).…”
Section: Pacs Numbersmentioning
confidence: 99%
See 2 more Smart Citations